Problems Encountered by School-Based Feeding Program Beneficiaries and Their Academic Performance - Vizcocho, Daren Joy D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Based Feeding Program beneficiaries and their academic performance in selected public school of Subic. This study was limited only to the three hundred forty (340) SBFP recipients of grade 4-6 elementary students in the District of Subic who were randomly selected. The study used descriptive survey method design. The major findings include the following: There was significant difference between the academic performance of students before and after the implementation of the school-based feeding program. Social, Behavioral and Economic problems encountered had low negative relationship with academic performance of beneficiaries before and after the implementation. The null hypothesis was rejected; hence there is significant relationship between the problems encountered and the academic performance of SBFP. The following recommendations are Employed parents may not take their child’s health nutritional status for granted by ensuring enough time to supervise their feeding habits of their child. School feeding coordinators may also look into the problems of the beneficiaries and not just providing them food during feeding time. School advisers and teachers may collaborate with parents/guardian of the SBFP beneficiaries in minimizing and eliminating the sources and cause of problems to attain higher level, if not the highest level of academic performance.